Venous ulcer treatment requires inelastic compression - Mosti, G. (Phlebologie, 2018)
Leg ulcers have a venous pathophysiology in the vast majority of cases (1–4). Superficial or deep venous insufficiency and deep vein obstruction produce ambulatory venous hypertension due to venous reflux and venous pumping function impairment. The impaired venous hemodynamics is the key pathophysiologic mechanism leading to skin damage through several intermediate steps. Fibrin cuff formation around the microvessels, impairing gases (O2, CO2) exchange (5), white cells entrapment (6) causing skin necrosis, growth factors inhibition (7) producing a stagnation of the healing process have been considered involved in ulcer onset and maintenance. The treatment of venous leg ulcers (VLU) must be based on the correction of the hemodynamic impairment which can be achieved conservatively by means of compression therapy, walking and leg elevation or by means of invasive procedures (open surgery, endovascular procedures as endovenous Laser ablation, radiofrequency, foam sclerotherapy, conservative hemodynamic treatment). Compression therapy is frequently considered the first treatment option and it is the only therapeutical procedure which achieved the grade 1A in most recent guidelines or consensus documents (8–10). The crucial point is choosing the most effective compression modality. There are clear evidences that inelastic is more effective than elastic material in counteracting the venous hemodynamic impairment (11–14) that should „ensure” a superior effectiveness in promoting a higher healing rate of VLU, which are due to venous hemodynamic impairment. When looking at evidences we have some data showing that the higher the compression pressure the higher the healing rate (9, 15–17) and this is clearly in favors of inelastic bandages which exert a much higher pressure that elastic materials. On the other side we have many papers claiming a greater effectiveness of elastic stockings or elastic bandaged compared with inelastic material (18–30). Nevertheless studies comparing elastic and inelastic devices have so many flaws that their conclusions are hard to trust (31). Aim of this work is providing updated information about compression therapy effects on venous hemodynamic and the most effective compression modality to achieve the best outcome in VLU treatment.
Keywords: Venous leg ulcers; ulcer healing rate; compression therapy; elastic compression; inelastic compression; venous reflux; venous pumping function; venous hemodynamic impairment